2021
DOI: 10.3389/fped.2021.663054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDC20 as a Novel Biomarker in Diagnosis and Treatment of Wilms Tumor

Abstract: Objective: Wilms tumor (WT) is a common malignant solid tumor in children. Many tumor biomarkers have been reported; however, there are poorly targetable molecular mechanisms which have been defined in WT. This study aimed to identify the oncogene in WT and explore the potential mechanisms.Methods: Differentially expressed genes (DEGs) in three independent RNA-seq datasets were downloaded from The Cancer Genome Atlas data portal and the Gene Expression Omnibus database (GSE66405 and GSE73209). The common DEGs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In addition, we assessed the expression of four IRGs among them in three human Wilms tumour cell lines and compared them with a normal renal epithelial cell line, suggesting potential targets for further study. Numerous independent studies have shown the expression level of several single-gene was strongly correlated with the prognosis of WT patients (49)(50)(51)(52). Additional information of comprehensive bioinformatics analysis, clinicopathological factors, and model analysis were needed to further enhance the prediction accuracy of the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we assessed the expression of four IRGs among them in three human Wilms tumour cell lines and compared them with a normal renal epithelial cell line, suggesting potential targets for further study. Numerous independent studies have shown the expression level of several single-gene was strongly correlated with the prognosis of WT patients (49)(50)(51)(52). Additional information of comprehensive bioinformatics analysis, clinicopathological factors, and model analysis were needed to further enhance the prediction accuracy of the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[51] In renal cancer, CDC20 promotes proliferation by increasing the protein levels of securin, cyclin B1, and cyclin A. [55] In addition, CYP1B1 may promote renal cell proliferation, migration, and invasion, and inhibit apoptosis by inducing CDC20 expression. [56] miR-182-5 overexpression inhibits cell proliferation by directly targeting MALAT-1, then the downregulation of MALAT-1 leads to a decrease in CDC20.…”
Section: Role Of Cdc20 In Human Malignant Solid Tumorsmentioning
confidence: 99%
“…[56] Suppression of CDC20 slao inhibited migration and resulted in G2/M phase arrest in wilms tumor cells by increasing the expression levels of securin, cyclin B1, and cyclin A. [55] Moreover, several studies have shown that CDC20 knockdown can inhibit the invasion and metastasis of prostate cancer, [74] osteosarcoma, [75] cervical cancer, and ovarian cancer [69] (Table 1).…”
Section: Role Of Cdc20 In Human Malignant Solid Tumorsmentioning
confidence: 99%